PERSEPSI MAHASISWA FIP ANGKATAN 2011 TERHADAP PELAYANAN PERPUSTAKAAN PUSAT UNIVERSITAS NEGERI PADANG - Anggun Febia Mery (Jurnal Bahana Manajemen Pendidikan, 2015)
The goal of this research are to see perception of FIP’s student 2011 about the central library’s service in UNP. The population is 1.540 employees that taken by proportional random  sampling.  The instrument  of  this research  is  question  with Likert scale modelsthat  had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the employee has doing the perception of FIP’s student about the central library’s service in Padang State University stay in good category.Key word : central library’s service